2015
DOI: 10.1007/s11255-015-1043-8
|View full text |Cite|
|
Sign up to set email alerts
|

Intraocular pressure changes during hemodialysis

Abstract: The response of intraocular pressure (IOP) to hemodialysis procedure has been a subject of research throughout many decades. Several studies that evaluated the impact of hemodialysis (HD) on IOP have reported conflicting results and have drawn varied conclusions. Some studies have described an IOP elevation during HD, a finding they attributed to the osmotic disequilibrium between serum and aqueous humor induced by the HD procedure, especially when the facility of the outflow system is already compromised. On … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
16
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 26 publications
1
16
0
2
Order By: Relevance
“…There is controversy regarding the effect of hemodialysis on intraocular pressure. Although some studies have demonstrated that intraocular pressure may decrease or remain stable after hemodialysis 23 , most studies describe an increase in IOP during hemodialysis 15 16 17 18 . Various theories about the relationship between elevated IOP and hemodialysis have been postulated, and the most well-accepted theory suggests an influx of volume into the posterior chamber via the ciliary body due to an imbalance in osmolality between the ocular chamber and the blood during hemodialysis 24 .…”
Section: Discussionmentioning
confidence: 99%
“…There is controversy regarding the effect of hemodialysis on intraocular pressure. Although some studies have demonstrated that intraocular pressure may decrease or remain stable after hemodialysis 23 , most studies describe an increase in IOP during hemodialysis 15 16 17 18 . Various theories about the relationship between elevated IOP and hemodialysis have been postulated, and the most well-accepted theory suggests an influx of volume into the posterior chamber via the ciliary body due to an imbalance in osmolality between the ocular chamber and the blood during hemodialysis 24 .…”
Section: Discussionmentioning
confidence: 99%
“…The effects of hemodialysis on IOP changes remain uncertain. In 2015, Liakopoulos et al 10 published a review and discussed the changes in IOP in relation to hemodialysis in three groups: those with increased IOP, those with reduced IOP, and those without any change in IOP. Accordingly, the authors found that while the first studies had been carried out with longer and less effective hemodialysis systems, the development of more effective dialysis membranes and devices in recent years significantly prevented increases in IOP.…”
Section: Discussionmentioning
confidence: 99%
“…Alterations to the composition of vitreous humour in pseudophakic eyes after cataract surgery was discovered by Neal et al 22 and they suggested that these alterations may contribute to the retinal complications after cataract surgery. In ESRD patients, changes in intraocular pressure (IOP) [23][24][25] and ocular structures 26,27 during HD were reported in different studies. The ocular structure changes include decrease in choroidal thickness and retina thickness after HD.…”
Section: Discussionmentioning
confidence: 99%